Network coding schemes with efficient LDPC coded MIMO–NOMA in two-way relay networks - War Hlaing, Ngu; Farzamnia, Ali; Mariappan, Muralindran; Kumar Haldar, Manas (IET communications, 2020)
The combination of non-orthogonal multiple access (NOMA) and multi-input multi-output (MIMO) approaches has been considered as assuring multiple access for the fifth generation technology. In this study, the performance of a $2× 2$2×2 MIMO–NOMA system with low-density parity check (LDPC) codes is investigated. Redundancy with randomly interleaved differential encoding (R-RIDE) is proposed and applied to LDPC encoded messages by two users. LDPC decoding is done using the sum-product algorithm (SPA), which has two types of decoding methods, hard-decision and soft-decision. For hard-decision, bit-flipping decoder is used and for soft-decision, probability domain, log-domain, and simplified log-domain decoders are used. Bit error rate (BER) versus signal-to-noise ratio (SNR) in (dB) and average mutual information (AMI) in (bps/Hz) versus SNR (dB) are evaluated to compare the performance of the proposed and conventional LDPC schemes in NOMA and MIMO–NOMA systems. Simulation results show that both AMI and BER of the proposed LDPC–R-RIDE in MIMO–NOMA system greatly outperforms conventional LDPC coded schemes in NOMA and MIMO–NOMA systems. Moreover, the proposed R-RIDE-LDPC in MIMO-NOMA system outperforms the proposed scheme in the NOMA system. From the simulation results, LDPC–R-RIDE with simplified log-domain decoder has the best AMI result and BER performance compared with other decoding methods.